The Enhancement of Social Missions of Christian Organizations in Pattani Province - Tongsri, Prachuab; Sapsoontorngul, Arthit (Journal of Social Sciences and Humanities Research in Asia, 2021)
The objectives of this qualitative research were to 1) study the operating conditions of the social missions and 2) propose guidelines for developing the social missions of Christian organizations in Pattani Province through the use of participatory process. The data were collected from in-depth interviews and group discussions with 21 key informants, specifically selected from 6 churches in Pattani. A group chat was utilized to check data reliability, and a content analysis was employed in data analysis. The results showed that the social missions of the Christian organizations in Pattani Province are consistent with the principles of Christianity. They organize social activities on occasion which include both education and social work activities. The guidelines for developing their social missions are as follows: 1) Coordinating with potential leaders and personnel in strengthening the implementation of the organizations’ social missions, 2) Using existing opportunities in social work missions, 3) Developing the current staff in terms of concepts and skills in social missions work, public consciousness and social responsibility, and 4) Building a new generation of Christian leaders with a mindset of social missions.